The bureaucrats's decision rule and government efficiency - Zhang, Mengyang (Trinity College (Dublin, Ireland). Department of Economics, 2017)
This thesis focuses on the decision problem of local bureaucrats and the impact on government performance. Chapter 1 outlines the context of the thesis and provide a description of the thesis structure. Chapter 2 investigates the efficiency of decentralised targeting programmes and the distribution of public benefits. In Vietnam, village and commune officials decide whether a household is qualified to be classified as poor in order to get access to public transfers. This chapter focuses on the role of political connections in the poverty identification process and shows that political connections play a vital role. Households with relatives working in commune level government have an advantage in signalling their needs and are more likely to be classified as poor households. This is due to better knowledge of the process of identification. Social connections help identified households maintain social networks and reduce the probability of disagreement about the list and reporting corruption behaviour. Chapter 3 examines the effect of grand corruption, corruption at higher levels of government in China. Using a career concern model, there are underlying differences in the behaviour of politicians with different incentives. Rent seeking politicians are motivated to maximise private gain and raise fiscal revenue for the purpose of grabbing more rents. From 2002, the central government added individual and cooperate income taxes into the central-local shared tax category and took half of the income tax revenue from local governments. I use a difference-in-differences approach to compare the performance between rent-seeking and office-seeking politicians pre and post the policy change. The results show that provinces with more corrupt officials have relatively higher fiscal capacity. In contrast, office-seeking politicians prioritise career advancement over other targets and have a strong incentive to promote economic growth. I find that corrupt provinces have relatively lower fiscal capacity post-2001 due to the shrinking space for corruption after the increase in fiscal pressure. Chapter 4 focuses on the political incentives of provincial politicians in China. The performance-based promotion scheme has binding age limits on promotion prospects. As such, provincial officials change their incentives with age. The conceptual framework shows that officials change office-seeking motives to rent-seeking motives because of a negative expectation of future career progression. Using provincial data and the data on the characteristics and career paths of politicians, I confirm this incentive shift by showing that the growth rate of GDP dramatically drops at the cutoff age, while the focus on collecting revenue increases.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin